PENGARUH METODE LATIHAN TERHADAP KESEMPURNAAN TENDANGAN YEOPCHAGI PADA ATLET POOMSAE DOJANG TSU-DO CLUB SALATIGA - Zaneta, Lee Cesar Fyan (Journal of Sport Coaching and Physical Education, 2016)
There are so many methods to learn kicks. Methods that will be discussed are counting training methods and rubber resistance training method. The problems are 1) Is there any effect of counting training method to perfection of yeopchagi kick? 2) Is there any effect of rubber resistance training method to perfection of yeopchagi kick? 3) Which one is more effective between counting training method and rubber resistance training method to perfection of yeopchagi kick in Poomsae Athletes Salatiga Tsu-Do Club Dojang 2014?This is a quantitative research using experimental method. Data were analyzed by t-test statistic short formula. The population is poomsae athletes Salatiga Tsu-Do club dojang age 14-17 years. Sampling techniques is random sampling. There are two variables with the independent variables are counting training method and rubber resistance training method and bound variable is perfection of yeopchagi kick.The result of the study control group is t count < t table and experiment is t count > t table. There are differences in the mean both groups. The percentage difference in pre-test and post-test mean control group was 9% men and 13% women, while the experimental group was 12% men and 21% women. Hypothesis conclusions are 1) There is no effect of counting training method to perfection of yeopchagi kick, 2) There is an effect of rubber resistance training method to perfection of yeopchagi kick, 3) Rubber resistance training method is more effective than counting training method in Poomsae Athletes Salatiga Tsu-Do Club Dojang 2014. As for the suggestion to Tsu-do club dojang taekwondo coach to provide training materials to improve perfection of yeopchagi kick, to provide specific additional training as a method using this rubber, so the athletes will be trained and can produce a backlash that meets perfection factor kicks.